Learning english as a strategy to improve the competiveness for Professional Development in the Tourist and Hotel Management Industry, case Chicago, Illinois, USA - Silva Leon, Ludy Edikc (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (99 páginas) : ilustraciones color, tablas, figuras.